Allergic Rhinitis Is Associated With Periodontitis: A Population‐Based Study. Issue 7 (1st July 2016) - Hung, Shih‐Han; Tsai, Ming‐Chieh; Lin, Herng‐Ching; Chung, Shiu‐Dong
Abstract : Background: Little is known regarding associations of periodontitis with diseases of the nose, one of the structures adjacent to the mouth. This study aims to explore the association between periodontitis and previous allergic rhinitis (AR) using a matched patient–control study design from a population‐based dataset in Taiwan. Methods: Data were sourced from the Longitudinal Health Insurance Database 2000 for 71, 182 patients with chronic periodontitis (CP) and 71, 182 controls without periodontitis. Generalized linear mixed‐model analyses were used to calculate odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for previous AR diagnosis in patients and controls. Results: Significant difference was found in prevalence of prior AR for patients and controls (28.4% versus 24.2%; P <0.001). Generalized linear mixed model suggested that the OR of previous AR for patients was 1.24 (95% CI: 1.22 to 1.27; P <0.001) compared with controls. Adjustments were made for: 1) monthly income; 2) urbanization level; 3) diabetes mellitus; 4) hypertension; 5) coronary heart disease; 6) hyperlipidemia; 7) alcohol abuse; 8) tobacco use disorder; and 9) random effect of geographic region. After adjusting, OR of previous AR diagnosis among patients was 1.21 (95% CI: 1.18 to 1.23; P <0.001) compared with controls. Conclusions: An association between periodontitis and prior AR is demonstrated. It is recommended that physicians be more alert for potential risk of subsequent development of CP in patients with AR.